POLYCODE TEXT AS A SPACE OF CONFLICTOGENITY MANIFESTATION - Oleg A. Alimuradov; Maxim N. Latu; Aleksey V. Razduyev (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article is devoted to the identification of the linguasemiotic features of a polycode text as a space for manifestation of conflictogenicity. The novelty of the research consists in a detailed examination of the graphic and verbal components of a polycode conflict-generating text, establishing their correlations and identifying the most frequent mechanisms of creating conflictogenicity. It is argued that the emergence of a conflict potential in any text is conditioned by the fact that it builds a clear opposition “friend – foe”. Using memes and demotivators as a source the presence of certain verbal indices of conflictogenity is revealed, in particular, various lexical markers, such as lexical units of neutral and substandard register (slang, colloquial, obscene lexis), evaluative idiomatic expressions (including those with an occasionally reinterpreted external form), new lexical units (neologisms, occasionalisms, interlanguage borrowings), etc. The authors conclude that the visual components of polycode texts often more effectively convey a conflict-generating message than the verbal ones, being in this sense a powerful semantically loaded figure against the background of the verbal component. The analysis has resulted in revealing complement and contradiction to be especially relevant from a linguosemiotic point of view types of visual and verbal elements correlations in a polycode text, considered all the traditionally distinguished types of conflict-generating variety.